Causes of the Civil War [ the differences between the North and South - Mountjoy, Shane , 1967-; McNeese, Tim (Civil War : a nation divided., 2009)
Examines the sectional rivalries that surfaced in the early 19th century and intensified in the decades leading up to the war.